Polyorganosiloxane-containing polymer, composition, and molded body

JP7643536B2Active Publication Date: 2025-03-11MITSUBISHI CHEM CORP
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2023511235
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-03-30
Filing Date
2022-03-28
Publication Date
2025-03-11
Estimated Expiration
2042-03-28

AI Technical Summary

Benefits of technology

【0008】 本発明によれば、樹脂に添加した際に、耐衝撃特性を大幅に低下させることなく優れた難燃性を示す成形体を得ることができる、ポリオルガノシロキサン含有重合体を提供できる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007643536000001
    Figure 0007643536000001
  • Figure 0007643536000002
    Figure 0007643536000002
  • Figure 0007643536000003
    Figure 0007643536000003
Patent Text Reader

Abstract

Provided is a polyorganosiloxane-containing polymer from which it is possible to, when a resin is added thereto, obtain a molded article having excellent fire resistance without causing a significant deterioration in impact resistance properties. The polyorganosiloxane-containing polymer according to the present invention contains 100 mass ppm or more of alkali metal atoms, and has a mass average particle diameter Dw of 350 nm or more.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polyorganosiloxane-containing polymer, a composition, and a molded article. This application claims priority to Japanese Patent Application No. 2021-056873, filed in Japan on March 30, 2021, the contents of which are incorporated herein by reference. [Background technology]

[0002] Rubber-containing polymers, in which vinyl monomers are polymerized on rubber polymers, can be dispersed in a wide variety of resins while maintaining a specified rubber particle size and rubber structure, and are therefore suitable for use in resins requiring impact strength.

[0003] Among them, silicone rubber is less likely to harden or discolor due to heat or ultraviolet light and has excellent durability compared to butadiene rubber, and is therefore preferably used in applications requiring long-term maintenance of mechanical properties such as building materials and automobile parts. Polyorganosiloxanes, typified by polydimethylsiloxane, are used as silicone rubbers, and various graft copolymers using rubbers containing such polyorganosiloxanes are known.

[0004] Patent Document 1 describes a polyorganosiloxane-containing graft copolymer having a specific glass transition temperature (Tg), which is obtained by graft polymerizing a monofunctional vinyl monomer and a polyfunctional vinyl monomer in a specific ratio onto a rubber containing polyorganosiloxane. Patent Document 2 describes a polyorganosiloxane-containing graft copolymer having a volume average particle size of 300 to 2000 nm and a polyorganosiloxane content of 70 to 98 mass %. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] International Publication No. 2018 / 225582 [Patent Document 2] International Publication No. 2013 / 162080 Summary of the Invention [Problem to be solved by the invention]

[0006] When the polyorganosiloxane-containing polymer described in Patent Document 1 or 2 is added to a resin, there are cases where the flame retardancy of the resulting molded article is problematic. Also, when a flame retardant such as a metal salt is added to a thermoplastic resin in addition to the polyorganosiloxane-containing polymer in order to improve the flame retardancy, the impact resistance may be significantly reduced. An object of the present invention is to provide a polyorganosiloxane-containing polymer which, when added to a resin, can give a molded article exhibiting excellent flame retardancy without significantly decreasing impact resistance. [Means for solving the problem]

[0007] The present invention has the following aspects. [1] A polyorganosiloxane-containing polymer containing 100 ppm by mass or more of alkali metal atoms and having a mass average particle diameter Dw of 350 nm or more. [2] The polyorganosiloxane-containing polymer of [1], having a mass average particle diameter Dw of 1000 nm or less. [3] A polymer having a complex and a graft portion, The composite includes a polyorganosiloxane and a first vinyl polymer; The polyorganosiloxane-containing polymer according to [1] or [2], wherein the graft portion contains a second vinyl polymer. [4] The polyorganosiloxane-containing polymer according to [3], wherein the proportion of the graft portion in 100 mass% of the polyorganosiloxane-containing polymer is 5 mass% or more and 20 mass% or less. [5] The polyorganosiloxane-containing polymer according to [3] or [4], wherein the first vinyl polymer contains a structural unit derived from a (meth)acrylate monomer. [6] The polyorganosiloxane-containing polymer according to any one of [3] to [5], wherein the second vinyl polymer contains a structural unit derived from a (meth)acrylate monomer. [7] The polyorganosiloxane-containing polymer according to any one of [3] to [6], wherein the polyorganosiloxane contains a structural unit derived from a siloxane-based crosslinking agent, and the proportion of the structural unit derived from the siloxane-based crosslinking agent in 100 mass% of the polyorganosiloxane is 3 mass% or less. [8] The polyorganosiloxane-containing polymer according to any one of [1] to [7], wherein the proportion of polyorganosiloxane in 100 mass% of the polyorganosiloxane-containing polymer is 70 mass% or more and 98 mass% or less. [9] The polyorganosiloxane-containing polymer according to any one of [1] to [8], wherein the alkali metal atom is a sodium atom.

[10] A polyorganosiloxane-containing polymer according to any one of [1] to [9], which is in powder form.

[11] A composition comprising the polyorganosiloxane-containing polymer according to any one of [1] to

[10] and a thermoplastic resin.

[12] A molded article comprising the polyorganosiloxane-containing polymer according to any one of [1] to

[10] and a thermoplastic resin. Effect of the Invention

[0008] According to the present invention, there is provided a polyorganosiloxane-containing polymer which, when added to a resin, can give a molded article exhibiting excellent flame retardancy without significantly decreasing impact resistance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] Hereinafter, the embodiments of the present invention will be described in detail, but the present invention is not limited to these descriptions, and other than the following examples, modifications and variations can be made as appropriate without departing from the spirit of the present invention. In the present invention, the vinyl monomer means a compound having a polymerizable double bond. In the present invention, (meth)acrylic means one or both of acrylic and methacrylic, and (meth)acrylic acid ester means one or both of acrylic acid ester and methacrylic acid ester. In this specification, the symbol "to" is used to mean that the numerical values ​​before and after it are included as lower and upper limits. In other words, a numerical value expressed as "A to B" means A or more and B or less.

[0010] <Polyorganosiloxane-containing polymer> The polyorganosiloxane-containing polymer according to one embodiment of the present invention (hereinafter also referred to as "polymer (C)") comprises a polymer (A) and a second vinyl polymer (B) (hereinafter also referred to as "vinyl polymer (B)"). The polymer (A) is preferably a complex containing at least a polyorganosiloxane (A1) and further containing a first vinyl polymer (A2) (hereinafter also referred to as "vinyl polymer (A2)"). The polyorganosiloxane (A1) and the vinyl polymer (B) are preferably at least partially crosslinked. The polyorganosiloxane-containing polymer is preferably a graft copolymer having a complex (composite rubber-like polymer) of the polyorganosiloxane (A1) and the vinyl polymer (A2) and a graft portion containing the vinyl polymer (B1).

[0011] The polymer (C) contains alkali metal atoms in an amount of 100 ppm by mass or more and has a mass average particle diameter Dw of 350 nm or more. In the present invention, the amount of alkali metal atoms is measured according to the measurement method described in the Examples. The mass average particle size is measured according to the method described in the Examples. As a result, when a molded article is produced by blending the polyolefin with a resin, it is possible to provide a molded article that has high impact resistance, high flame retardancy, and excellent appearance.

[0012] When an alkali metal atom is present on the surface of the polyorganosiloxane-containing polymer, the thermal decomposition property of the polyorganosiloxane-containing polymer tends to improve. In addition, when the particle size of the polyorganosiloxane-containing polymer is large, the thickness of the vinyl polymer (B) increases, so that the dispersion in the resin tends to be excellent. Here, the polyorganosiloxane-containing polymer uniformly dispersed in the resin composition is instantly decomposed near the decomposition temperature of the resin to form a dense carbonized layer, which is considered to improve the flame retardancy of the molded body.

[0013] The polyorganosiloxane-containing polymer can be obtained as a powdered polymer by performing a process including drying after obtaining a latex-like polymer as described below. However, depending on the processing method, even if the latex-like polyorganosiloxane-containing polymer contains alkali metal atoms, the amount of alkali metal contained in the obtained powdered polymer may be reduced. Therefore, in order to exhibit the above-mentioned effect, it is preferable that the polyorganosiloxane-containing polymer when producing the resin composition, that is, the powdered polyorganosiloxane-containing polymer, is a powder group containing a polyorganosiloxane-containing polymer that contains 100 ppm or more of alkali metal atoms and has a mass average particle diameter Dw of 350 nm or more.

[0014] The mass average particle diameter Dw of the polyorganosiloxane-containing polymer is 350 nm or more, preferably 375 nm or more, and more preferably 400 nm or more, in order to improve the appearance and wet heat resistance. The mass average particle diameter Dw of the polyorganosiloxane-containing polymer is preferably 1000 nm or less, more preferably 800 nm or less, even more preferably 600 nm or less, and particularly preferably 500 nm or less, in order to improve productivity. The above upper and lower limits can be arbitrarily combined. For example, 350 to 1000 nm is preferable, 350 to 800 nm is more preferable, 375 to 600 nm is more preferable, and 400 to 500 nm is particularly preferable.

[0015] The amount of alkali metal atoms contained in the polyorganosiloxane-containing polymer is 100 mass ppm or more, preferably 150 mass ppm or more, and more preferably 200 mass ppm or more, in order to improve flame retardancy and wet heat resistance. The amount of alkali metal atoms contained in the polyorganosiloxane-containing polymer is preferably 1000 mass ppm or less, more preferably 800 mass ppm or less, even more preferably 600 mass ppm or less, and particularly preferably 400 mass ppm or less, in order to improve impact resistance. The above upper and lower limits can be arbitrarily combined. For example, 100 to 1000 mass ppm is preferred, 100 to 800 mass ppm is more preferred, 150 to 600 mass ppm is more preferred, and 200 to 400 mass ppm is particularly preferred.

[0016] The alkali metal is not particularly limited, and examples thereof include lithium atom, sodium atom, potassium atom, rubidium atom, and cesium atom. The polyorganosiloxane-containing polymer may contain one type of alkali metal atom, or may contain two or more types of alkali metal atoms. When the polyorganosiloxane-containing polymer contains two or more types of alkali metal atoms, the amount of alkali metal atoms contained in the polyorganosiloxane-containing polymer means the total mass of alkali metal atoms. The alkali metal atom is preferably a lithium atom, a sodium atom, or a potassium atom, and particularly preferably a sodium atom.

[0017] The polyorganosiloxane-containing polymer may contain alkaline earth metals and aluminum due to the manufacturing method. Since alkaline earth metals and aluminum are impurities, it is preferable that the content of alkaline earth metals and aluminum in the polyorganosiloxane-containing polymer is small, but the effect of the alkaline earth metal and aluminum content on the present invention is small. On the other hand, since the process may become complicated when trying to remove alkaline earth metals and aluminum from the polyorganosiloxane-containing polymer, the content of alkaline earth metals and aluminum in the polyorganosiloxane-containing polymer may be 150 ppm or more, 100 ppm or more, 50 ppm or more, 0 ppm or more, or 0 ppm, respectively, from the viewpoint of improving productivity.

[0018] (Polyorganosiloxane (A1)) The polyorganosiloxane (A1) is a polymer containing an organosiloxane unit. The organosiloxane unit means a Si-O unit to which an organic group is bonded. The polyorganosiloxane has a structure represented by the following formula (1).

[0019] [ka]

[0020] In formula (1), R 1 and R 2 each independently represents a hydrogen atom, a halogen atom, or a monovalent organic group; R 1 and R 2 At least one of the groups is a monovalent organic group. n represents an integer of 2 or more.

[0021] The polyorganosiloxane (A1) can be obtained by polymerizing an organosiloxane mixture containing an organosiloxane. The organosiloxane mixture may further contain components that are used as necessary. Examples of components that may be used as needed include a siloxane crosslinking agent, a siloxane crosslinking agent, and a siloxane oligomer having a terminal blocking group.

[0022] Examples of organosiloxanes include linear organosiloxanes, alkoxysilane compounds, and cyclic organosiloxanes. Alkoxysilane compounds and cyclic organosiloxanes are preferred, and cyclic organosiloxanes are more preferred because of their high polymerization stability and high polymerization rate.

[0023] The alkoxysilane compound is preferably a bifunctional alkoxysilane compound. For example, dimethyldimethoxysilane, dimethyldiethoxysilane, diethoxydiethylsilane, dipropoxydimethylsilane, diphenyldimethoxysilane, diphenyldiethoxysilane, methylphenyldimethoxysilane, and methylphenyldiethoxysilane can be mentioned. The alkoxysilane compound can be used alone or in combination of two or more.

[0024] The cyclic organosiloxane is preferably a cyclic organosiloxane having a 3-7 member ring. For example, hexamethylcyclotrisiloxane, octamethylcyclotetrasiloxane, decamethylcyclopentasiloxane, dodecamethylcyclohexasiloxane, trimethyltriphenylcyclotrisiloxane, tetramethyltetraphenylcyclotetrasiloxane, and octaphenylcyclotetrasiloxane can be mentioned. The cyclic organosiloxane can be used alone or in combination of two or more. Octamethylcyclotetrasiloxane is preferred because it is easy to control the particle size distribution.

[0025] As the organosiloxane, from the viewpoint of obtaining a polymer (C) capable of increasing the impact strength of a molded article, at least one selected from the group consisting of cyclic dimethylsiloxane and bifunctional dialkylsilane compounds is preferred.

[0026] Cyclic dimethylsiloxane is a cyclic siloxane having two methyl groups on a silicon atom. For example, hexamethylcyclotrisiloxane, octamethylcyclotetrasiloxane, decamethylcyclopentasiloxane, and dodecamethylcyclohexasiloxane can be mentioned. Cyclic dimethylsiloxane can be used alone or in combination of two or more.

[0027] A bifunctional dialkylsilane compound is a silane compound having two alkoxy groups and two alkyl groups on a silicon atom. Examples include dimethyldimethoxysilane, dimethyldiethoxysilane, diethoxydiethylsilane, and dipropoxydimethylsilane. The bifunctional dialkylsilane compound can be used alone or in combination of two or more.

[0028] The siloxane crosslinking agent is preferably one having a siloxy group. Examples of the siloxane crosslinking agent include trifunctional or tetrafunctional silane crosslinking agents such as trimethoxymethylsilane, triethoxyphenylsilane, tetramethoxysilane, tetraethoxysilane, tetra-n-propoxysilane, and tetrabutoxysilane. The tetrafunctional crosslinking agent is preferred, and tetraethoxysilane is more preferred.

[0029] The proportion of the siloxane crosslinking agent in 100% by mass of the organosiloxane mixture, i.e., the proportion of the structural unit derived from the siloxane crosslinking agent in 100% by mass of the polyorganosiloxane, is not particularly limited, and in order to improve flame retardancy, it is preferably 10% by mass or less, more preferably 3% by mass or less, even more preferably 0.5% by mass or less, and may be 0% by mass. If the proportion of the siloxane crosslinking agent is equal to or less than the upper limit, the impact strength of the obtained molded article is easily improved.

[0030] The siloxane crosslinking agent has a siloxy group (-Si-O-) and a functional group polymerizable with a vinyl monomer. Examples of the siloxane crosslinking agent include siloxanes represented by the following formula (I). R-Si(R 1 )n (OR 2 ) (3-n) (I) In formula (I), R 1 R represents a methyl group, an ethyl group, a propyl group, or a phenyl group. 2 represents an organic group such as a hydrocarbon group, and is preferably, for example, a methyl group, an ethyl group, a propyl group, or a phenyl group. n represents 0, 1, or 2. R represents a functional group represented by any one of the following formulas (I-1) to (I-4). CH2=C(R 3 )-COO-(CH2) p - (I-1) CH2=C(R 4 )-C6H4- ···(I-2) CH2=CH- (I-3) HS-(CH2) p - (I-4) In these formulas, R 3 and R 4 each independently represents a hydrogen atom or a methyl group, and p represents an integer of 1 to 6.

[0031] The functional group represented by formula (I-1) can be exemplified by methacryloyloxyalkyl group.The siloxane having the group represented by formula (I-1) can be exemplified by β-methacryloyloxyethyldimethoxymethylsilane, γ-methacryloyloxypropylmethoxydimethylsilane, γ-methacryloyloxypropyldimethoxymethylsilane, γ-methacryloyloxypropyltrimethoxysilane, γ-methacryloyloxypropylethoxydiethylsilane, γ-methacryloyloxypropyldiethoxymethylsilane, δ-methacryloyloxybutyldiethoxymethylsilane. An example of the functional group represented by formula (I-2) is a vinylphenyl group. An example of the siloxane having a group represented by formula (I-2) is vinylphenylethyldimethoxysilane. Examples of siloxanes having a functional group represented by formula (I-3) include vinyltrimethoxysilane and vinyltriethoxysilane. The functional group represented by formula (I-4) may be a mercaptoalkyl group. Examples of the siloxane having a group represented by formula (I-4) include γ-mercaptopropyl dimethoxymethylsilane, γ-mercaptopropyl methoxydimethylsilane, γ-mercaptopropyl diethoxymethylsilane, γ-mercaptopropyl ethoxydimethylsilane, and γ-mercaptopropyl trimethoxysilane.

[0032] The siloxane-based crosslinking agent may be used alone or in combination of two or more kinds. As the siloxane-based crosslinking agent, γ-methacryloyloxypropylmethyldimethoxysilane is preferred because it is easy to form an island structure when the polyorganosiloxane (A1) and the vinyl polymer (A2) are composited.

[0033] When the organosiloxane mixture contains a siloxane crossing agent, the ratio of the siloxane crossing agent in 100% by mass of the organosiloxane mixture is preferably 0.05% by mass or more, more preferably 0.1% by mass or more, and even more preferably 0.5% by mass or more. The ratio of the siloxane crossing agent in 100% by mass of the organosiloxane mixture is preferably 20% by mass or less, more preferably 10% by mass or less, and even more preferably 5% by mass or less. The above upper and lower limits can be arbitrarily combined. For example, 0.05 to 20% by mass is preferred, 0.1 to 10% by mass is more preferred, and 0.5 to 5% by mass is even more preferred. If the ratio of the siloxane graft crossing agent is within the range of the upper limit value and the lower limit value, the covalent bond between the polyorganosiloxane (A1) and the vinyl polymer (A2) can be sufficiently formed, and a polymer (C) having good impact strength can be obtained.

[0034] The mass average particle diameter of the polyorganosiloxane (A1) is preferably 100 nm or more, more preferably 200 nm or more, and even more preferably 300 nm or more. The mass average particle diameter of the polyorganosiloxane (A1) is preferably 1000 nm or less, more preferably 800 nm or less, and even more preferably 600 nm or less. The above upper and lower limits can be arbitrarily combined. For example, 100 to 1000 nm is preferable, 200 to 800 nm is more preferable, and 300 to 600 nm is more preferable. If the mass average particle diameter of the polyorganosiloxane (A1) is within the range of the upper limit value and the lower limit value, it is easy to adjust the mass average particle diameter of the polymer (C) within the range of the preferable upper limit value and the lower limit value.

[0035] <Method for producing polyorganosiloxane (A1)> The method for producing the polyorganosiloxane (A1) is not particularly limited, and for example, a production method (M) can be used in which an organosiloxane mixture containing an organosiloxane, a siloxane-based crosslinking agent if necessary, a siloxane-based crosslinking agent if necessary, and a siloxane oligomer having a terminal blocking group if necessary is emulsified with an emulsifier and water to prepare an emulsion, and in this emulsion, the organosiloxane mixture is polymerized at high temperature in the presence of an acid catalyst, and then the acid catalyst is neutralized with an alkaline substance to obtain a polyorganosiloxane latex. In the following description, the case where an "organosiloxane mixture" is used as the raw material for polymerization will be described. The same manufacturing process can also be applied to the case where an "organosiloxane" is used as the raw material for polymerization.

[0036] In the manufacturing method (M), the preparation method of the emulsion can be, for example, the method of atomizing by shearing force by high speed rotation, for example, the method of using a homomixer; the method of atomizing by the ejection force of a high pressure generator, for example, the method of mixing by high speed stirring using a homogenizer; The method of using a homogenizer is preferred because it is easy to narrow the particle size distribution of the polyorganosiloxane latex.

[0037] The method of mixing the acid catalyst during polymerization includes, for example, a method of adding the acid catalyst together with the organosiloxane mixture, the emulsifier, and water all at once and mixing them (Method 1); a method of adding an aqueous acid catalyst solution all at once to an emulsion of the organosiloxane mixture (Method 2); and a method of dropping the emulsion of the organosiloxane mixture into a high-temperature aqueous acid catalyst solution at a constant speed and mixing them (Method 3). Method 3 is preferred because it is easy to control the particle size of the polyorganosiloxane.

[0038] The polymerization temperature is preferably 50° C. or higher, more preferably 70° C. or higher. The upper limit of the polymerization temperature is, for example, 100° C. When polymerization is carried out using Method 3, the polymerization time is usually 2 hours or more, preferably 5 hours or more.

[0039] At temperatures below 30°C, the crosslinking reaction between silanols proceeds, so in order to increase the crosslink density of the polyorganosiloxane, the latex formed after polymerization at a high temperature of 50°C or higher can be kept at a temperature below 30°C for about 5 to 100 hours.

[0040] The polymerization reaction of the organosiloxane mixture can be terminated by neutralizing the reaction system containing the latex to a pH of 6 to 8 with an alkaline substance such as sodium hydroxide, potassium hydroxide, or an aqueous ammonia solution.

[0041] The emulsifier is not particularly limited as long as it is capable of emulsifying the organosiloxane mixture, and anionic emulsifiers or nonionic emulsifiers are preferred. Examples of the anionic emulsifier include sodium alkylbenzene sulfonate, sodium alkyl diphenyl ether disulfonate, sodium alkyl sulfate, sodium polyoxyethylene alkyl sulfate, and sodium polyoxyethylene nonylphenyl ether sulfate. Examples of the nonionic emulsifier include polyoxyethylene alkyl ether, polyoxyethylene alkylene alkyl ether, polyoxyethylene distyrenated phenyl ether, polyoxyethylene tribenzyl phenyl ether, and polyoxyethylene polyoxypropylene glycol. The emulsifiers can be used alone or in combination of two or more.

[0042] The amount of the emulsifier used is preferably 0.05 parts by mass or more, more preferably 0.1 parts by mass or more, relative to 100 parts by mass of the organosiloxane mixture. The amount of the emulsifier used is preferably 20 parts by mass or less, more preferably 10 parts by mass or less, relative to 100 parts by mass of the organosiloxane mixture. The upper and lower limits can be arbitrarily combined. For example, 0.05 to 20 parts by mass is preferred, and 0.1 to 10 parts by mass is more preferred. Depending on the amount of the emulsifier used, it is possible to adjust the particle size of the polyorganosiloxane latex to a desired value. Increasing the amount of the emulsifier can reduce the particle size, and decreasing the amount of the emulsifier can increase the particle size. If the amount of the emulsifier used is equal to or more than the lower limit, the emulsion stability of the emulsion of the organosiloxane mixture can be improved. If the amount of the emulsifier used is equal to or less than the upper limit, the heat discoloration resistance and surface appearance of the molded product are excellent.

[0043] Examples of acid catalysts used in the polymerization of the organosiloxane mixture include sulfonic acids such as aliphatic sulfonic acid, aliphatic-substituted benzenesulfonic acid, and aliphatic-substituted naphthalenesulfonic acid; and mineral acids such as sulfuric acid, hydrochloric acid, and nitric acid. The acid catalysts can be used alone or in combination of two or more. The use of mineral acids makes it easier to narrow the particle size distribution of the polyorganosiloxane latex, and also makes it easier to suppress the occurrence of problems (such as a decrease in thermal decomposition resistance of the molded product and poor appearance) caused by the emulsifier component in the polyorganosiloxane latex.

[0044] The amount of the acid catalyst used is preferably 0.005 parts by mass or more and 40 parts by mass or less per 100 parts by mass of the organosiloxane. If the amount of the acid catalyst used is 0.005 parts by mass or more, the organosiloxane mixture can be polymerized in a short time. If the amount of the acid catalyst used is 40 parts by mass or less, the heat discoloration resistance and surface appearance of the molded product are excellent.

[0045] Since the amount of the acid catalyst used is a factor that determines the particle size of the polyorganosiloxane (A1), in order to obtain a polyorganosiloxane (A1) having a particle size described below, it is more preferable to use an amount of the acid catalyst of 1 part by mass or more and 30 parts by mass or less per 100 parts by mass of the organosiloxane. Note that, if the amount of the acid catalyst used is small, the particle size tends to be large.

[0046] To the polyorganosiloxane latex obtained by the production method (M), an emulsifier may be added as necessary for the purpose of improving mechanical stability. As the emulsifier, the same anionic emulsifiers and nonionic emulsifiers as those exemplified above are preferred.

[0047] (Vinyl polymer (A2)) The polymer (A) may contain a vinyl polymer (A2). When the polymer (A) contains a vinyl polymer (A2), the polymer (A) may be a polymer in which the vinyl polymer (A2) and the polyorganosiloxane (A1) are crosslinked, or may be a composite polymer in which the polyorganosiloxane (A1) and the vinyl polymer (A2) are not crosslinked, and it is preferable that the vinyl polymer (A2) and the polyorganosiloxane (A1) are crosslinked.

[0048] The vinyl polymer (A2) is a polymer obtained by polymerization of the vinyl monomer component (a2), i.e., the vinyl polymer (A2) contains vinyl monomer units derived from the vinyl monomer component (a2). The vinyl monomer component (a2) constituting the first vinyl polymer (A2) may be one type of vinyl monomer or two or more types of vinyl monomers.

[0049] From the viewpoint of the impact strength of a molded article, the vinyl monomer component (a2) preferably contains a (meth)acrylate monomer (hereinafter also referred to as "monomer (a2-1)").

[0050] The monomer (a2-1) is not particularly limited, and preferably includes (meth)acrylates in which the carbon number of the alkyl group is 1 to 20. For example, alkyl acrylates such as methyl acrylate, ethyl acrylate, n-propyl acrylate, n-butyl acrylate, 2-ethylhexyl acrylate, and n-octyl acrylate; alkyl methacrylates such as methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, n-butyl methacrylate, i-butyl methacrylate, t-butyl methacrylate, hexyl methacrylate, 2-ethylhexyl methacrylate, lauryl methacrylate, tridecyl methacrylate, and stearyl methacrylate;

[0051] The (meth)acrylate is preferably an alkyl acrylate having a carbon number of 1 to 20. In order to improve the impact strength of a molded article, the number of carbon atoms in the alkyl group of the alkyl acrylate is preferably 2 or more, more preferably 3 or more, and even more preferably 4 or more, and is preferably 16 or less, more preferably 12 or less, and even more preferably 8 or less. n-Butyl acrylate is particularly preferable. The monomer (a2-1) can be used alone or in combination of two or more kinds.

[0052] When the vinyl monomer component (a2) contains the monomer (a2-1), it may contain other monomers. Examples of the other monomers include a polyfunctional monomer (hereinafter, also referred to as "monomer (a2-2)") that can be copolymerized with the monomer (a2-1). From the viewpoint of the impact strength of the molded article, it is preferable that the vinyl monomer component (a2) contains the monomer (a2-1) and the monomer (a2-2).

[0053] The monomer (a2-2) is not particularly limited, and may be (meth)acrylate or cyanurate. The (meth)acrylate may be, for example, ethylene glycol dimethacrylate, propylene glycol dimethacrylate, ethylene glycol diacrylate, propylene glycol diacrylate, or allyl methacrylate. The cyanurate may be, for example, triallyl cyanurate or triallyl isocyanurate.

[0054] Allyl methacrylate, triallyl cyanurate, and triallyl isocyanurate are preferred, and allyl methacrylate is more preferred, since the impact strength of the molded article is improved. The monomer (a2-2) can be used alone or in combination of two or more kinds.

[0055] The proportion of the monomer (a2-1) in 100% by mass of the vinyl monomer component (a2) is not particularly limited, and from the viewpoint of improving the impact strength of the molded article, it is preferably 60% by mass or more, more preferably 70% by mass or more, even more preferably 80% by mass or more, and particularly preferably 90% by mass or more. The proportion of the monomer (a2-1) in 100% by mass of the vinyl monomer component (a2) is 100% by mass or less, preferably 99.9% by mass or less. The above upper and lower limits can be arbitrarily combined. For example, it is preferably 60 to 100% by mass, more preferably 70 to 100% by mass, even more preferably 80 to 99.9% by mass, and particularly preferably 90 to 99.9% by mass.

[0056] The proportion of the monomer (a2-2) in 100% by mass of the vinyl monomer component (a2) is not particularly limited, but in order to improve impact strength, it is preferably 0.1% by mass or more, and more preferably 2% by mass or less.

[0057] The vinyl monomer component (a2) may contain another monomer (a2-3) other than the monomer (a2-1) and the monomer (a2-2). The other monomer (a2-3) is not particularly limited, and examples thereof include aromatic vinyl monomers, vinyl cyanide monomers, and (meth)acrylic group-modified silicones.

[0058] The aromatic vinyl monomer is not particularly limited, and examples thereof include styrene and α-methylstyrene. The vinyl cyanide monomer is not particularly limited, and examples thereof include acrylonitrile and methacrylonitrile. The other monomers (a2-3) can be used alone or in combination of two or more.

[0059] (Polymer (A)) The polymer (A) contains a polyorganosiloxane (A1) and a vinyl polymer (A2). The polymer (A) preferably functions as a composite rubber of the polyorganosiloxane (A1) and the vinyl polymer (A2). In order to function as a composite rubber, it is preferable that the glass transition temperatures (hereinafter sometimes referred to as Tg) of the polyorganosiloxane (A1) and the vinyl polymer (A2) are each 0°C or lower.

[0060] In the polymer (A), the mass ratio of polyorganosiloxane (A1) / vinyl polymer (A2) is preferably 50 / 50 or more, more preferably 70 / 98 or more, and preferably 99 / 1 or less, more preferably 95 / 5 or less, from the viewpoint of impact strength and flame retardancy of the molded article. The above upper and lower limits can be arbitrarily combined. For example, it is preferably 50 / 50 to 99 / 1, more preferably 70 / 98 to 95 / 5.

[0061] <Method for producing polymer (A)> The method for producing the polymer (A) is not particularly limited, but a method in which a vinyl monomer component (a2) constituting the vinyl polymer (A2) is polymerized in the presence of a latex containing polyorganosiloxane (A1) is preferred because the impact strength of the molded product is excellent.

[0062] The method of polymerizing the vinyl monomer component (a2) in the presence of the latex containing polyorganosiloxane (A1) is not particularly limited, and examples thereof include a method of dropping the vinyl monomer component (a2) into the latex containing polyorganosiloxane (A1) and polymerizing it (method i); a method of adding a part of the vinyl monomer component (a2) into the latex containing polyorganosiloxane (A1) under conditions that do not initiate polymerization, impregnating the particles of the polyorganosiloxane (A1), and then initiating polymerization, and then dropping or adding the remaining part of the vinyl monomer component (a2) all at once and polymerizing it (method ii); a method of adding the entire amount of the vinyl monomer component (a2) into the latex containing polyorganosiloxane (A1) under conditions that do not initiate polymerization, impregnating the particles of the polyorganosiloxane (A1), and then polymerizing it (method iii). Method iii is preferred because the impact strength of the molded product is excellent.

[0063] The method for producing the vinyl polymer (A2) is not particularly limited, and examples thereof include a method in which a vinyl monomer (a2) is polymerized by emulsion polymerization, suspension polymerization, or fine suspension polymerization, with the emulsion polymerization being preferred.

[0064] The radical polymerization initiator used for the polymerization of the vinyl monomer (a2) may be an azo initiator, a peroxide, or a redox initiator in which a peroxide and a reducing agent are combined. The radical polymerization initiator may be used alone or in combination of two or more. Azo initiators and redox initiators are preferred.

[0065] Examples of the azo initiator include oil-soluble azo initiators such as 2,2'-azobisisobutyronitrile, dimethyl 2,2'-azobis(2-methylpropionate), 2,2'-azobis(2,4-dimethylvaleronitrile), and 2,2'-azobis(2-butyronitrile); water-soluble azo initiators such as 4,4'-azobis(4-cyanovaleric acid), 2,2'-azobis[N-(2-carboxymethyl)-2-methylpropionamidine]hydrate, 2,2'-azobis-(N,N'-dimethyleneisobutylamidine)dihydrochloride, and 2,2'-azobis[2-(2-imidazolin-2-yl)propane]dihydrochloride; and the like. These can be used alone or in combination of two or more.

[0066] Examples of the peroxide include inorganic peroxides such as hydrogen peroxide, potassium persulfate, and ammonium persulfate, and organic peroxides such as diisopropylbenzene hydroperoxide, p-menthane hydroperoxide, cumene hydroperoxide, t-butyl hydroperoxide, succinic acid peroxide, t-butyl peroxy neodecanoate, t-butyl peroxy neoheptanoate, t-butyl peroxy pivalate, 1,1,3,3-tetramethylbutyl peroxy-2-ethylhexanoate, and t-butyl peroxy-2-ethylhexanoate. The peroxides can be used alone or in combination of two or more.

[0067] When a peroxide is combined with a reducing agent to form a redox initiator, it is preferable to use the above-mentioned peroxide in combination with a reducing agent such as sodium formaldehyde sulfoxylate, L-ascorbic acid, fructose, dextrose, sorbose, inositol, and ferrous sulfate·ethylenediaminetetraacetic acid disodium salt. The redox initiators can be used alone or in combination of two or more.

[0068] The radical polymerization initiator used for polymerization of the vinyl monomer (a2) is preferably a radical polymerization initiator having a solubility in water at 20°C of 5 mass % or less, and more preferably a radical polymerization initiator having a solubility of 2 mass % or less, since this makes it easy to obtain a graft copolymer having excellent impact resistance.

[0069] Examples of radical polymerization initiators having a solubility of 5% by mass or less in water at 20° C. include cumene hydroperoxide, diisopropylbenzene hydroperoxide, p-menthane hydroperoxide, t-butyl peroxy neodecanoate, t-butyl peroxy neoheptanoate, t-butyl peroxy pivalate, 1,1,3,3-tetramethylbutyl peroxy-2-ethylhexanoate, t-butyl peroxy-2-ethylhexanoate, 2,2′-azobisisobutyronitrile, dimethyl 2,2′-azobis(2-methylpropionate), 2,2′-azobis(2,4-dimethylvaleronitrile), and 2,2′-azobis(2-butyronitrile). Radical polymerization initiators having a solubility of 5% by mass or less in water at 20° C. can be used alone or in combination of two or more.

[0070] The solubility of the radical polymerization initiator in water at 20° C. can be found from catalogs of various radical polymerization initiators.

[0071] When an azo-based initiator is used as the radical polymerization initiator, the amount of the azo-based initiator used is preferably 0.01 to 1 part by mass per 100 parts by mass of the total of the monomers. When a redox initiator is used as the radical polymerization initiator, the amount of the peroxide used is preferably 0.01 to 1 part by mass per 100 parts by mass of the total monomers.When a redox initiator is used as the radical polymerization initiator, the amount of the reducing agent used is preferably 0.01 to 1 part by mass per 100 parts by mass of the total monomers.

[0072] (Vinyl polymer (B)) The vinyl polymer (B) is a polymer obtained by polymerization of a vinyl monomer component (b), and is a polymer containing structural units derived from a vinyl monomer. The vinyl monomer component (b) constituting the vinyl polymer (B) may be one or more kinds of vinyl monomers.

[0073] The vinyl monomer constituting the vinyl monomer component (b) is not particularly limited, but preferably includes a (meth)acrylate monomer.

[0074] The (meth)acrylate monomer is not particularly limited, and may be an alkyl (meth)acrylate. When one or more vinyl monomers contain an alkyl (meth)acrylate such as methyl (meth)acrylate, the resulting graft copolymer tends to have excellent compatibility and dispersibility in thermoplastic resins such as polycarbonate resins. Examples of the alkyl (meth)acrylate include alkyl methacrylates such as methyl methacrylate, ethyl methacrylate, n-butyl methacrylate, and i-butyl methacrylate; methyl acrylate, ethyl acrylate, and n-butyl acrylate. The (meth)acrylate monomer may be used alone or in combination of two or more. The number of carbon atoms in the alkyl group of the alkyl (meth)acrylate is not particularly limited, and is preferably 1 or more, and preferably 12 or less, more preferably 6 or less, and even more preferably 4 or less. The above upper and lower limits can be arbitrarily combined. For example, 1 to 12 is preferable, 1 to 6 is more preferable, and 1 to 4 is even more preferable. Methyl methacrylate is particularly preferable.

[0075] The vinyl monomer component (b) may further include one or more monomers selected from the group consisting of polyfunctional vinyl monomers, aromatic vinyl monomers, and vinyl cyanide monomers.

[0076] Examples of the polyfunctional vinyl monomer include allyl (meth)acrylate, triallyl cyanurate, divinylbenzene, diallyl phthalate, and ethylene glycol di(meth)acrylate. The polyfunctional vinyl monomer may be used alone or in combination of two or more kinds.

[0077] The aromatic vinyl monomer is not particularly limited, and examples thereof include styrene and α-methylstyrene. The aromatic vinyl monomer may be used alone or in combination of two or more kinds.

[0078] The vinyl cyanide monomer is not particularly limited, and examples thereof include acrylonitrile and methacrylonitrile. The vinyl cyanide monomer may be used alone or in combination of two or more kinds.

[0079] The proportion of the (meth)acrylate monomer in 100% by mass of the vinyl polymer (B) is preferably 50% by mass or more, more preferably 70% by mass or more, even more preferably 80% by mass or more, particularly preferably 90% by mass or more, and may be 100% by mass.

[0080] The Tg of the vinyl polymer (B) is preferably 70° C. or higher, more preferably 80° C. or higher, even more preferably 90° C. or higher, and preferably 105° C. or lower. The above upper and lower limits can be arbitrarily combined. For example, it is preferably 70 to 105° C., more preferably 80 to 105° C., and even more preferably 90 to 105° C. When the Tg of the vinyl polymer (B) is equal to or higher than the above lower limit, the powder of the obtained polymer (C) has good fluidity and the like. The Tg of the vinyl polymer (B) can be adjusted by the types and ratio of the vinyl monomers constituting the vinyl monomer component (b).

[0081] The Tg of the vinyl polymer (B) is determined by the FOX formula. In this case, the Tg of the homopolymer of the vinyl monomer constituting the vinyl monomer component (b) can be, for example, the value described in "POLYMER HANDBOOK" (Wiley Interscience / 1999). The Tg of the homopolymer of the vinyl monomer not described in this document can be calculated using Bicerano's method "Prediction of Polymer Properties" (MARCEL DEKKER / 2002).

[0082] (Method for producing polymer (C)) The polymer (C) can be produced, for example, by polymerizing (graft polymerizing) the vinyl monomer component (b) in the presence of the polymer (A), thereby obtaining a polymer in which a part or the whole of the vinyl polymer (B) is grafted onto the polymer (A).

[0083] The method for producing the polymer (C) is not particularly limited, and a method of adding a vinyl monomer component (b) to the latex of the polymer (A) and polymerizing the vinyl monomer component (b) in the latex is preferred. The latex of the polymer (A) is preferably produced by polymerizing the vinyl monomer component (a2) in the presence of a latex containing the polyorganosiloxane (A1).

[0084] The conditions for polymerizing the vinyl monomer component (b) are not particularly limited, and conventional conditions can be applied, such as conditions of 45 to 95° C. and 0.1 to 10 hours.

[0085] The method of adding the vinyl monomer component (b) to the latex of the polymer (A) is not particularly limited, and dropwise addition is preferred because it can suppress the generation of cullets. The entire amount of the vinyl monomer component (b) may be added dropwise continuously, or the vinyl monomer component (b) may be added dropwise in several portions while providing a holding time during which the vinyl monomer component (b) is not added dropwise.

[0086] After polymerizing the vinyl monomer component (b), it is preferable to recover the polymer (C) as a powder (or a group of powders, or a group of powders containing impurities) from the resulting latex of the polymer (C). When recovering the polymer (C) as a powder, a direct drying method such as a spray drying method or a coagulation method can be used. In the direct drying method, the auxiliary agents added during polymerization can be generally allowed to remain in the obtained powder. In the coagulation method, the amount of polymerization auxiliary residues contained in the obtained powder, such as the emulsifier and its coagulation salt used during polymerization, and the initiator, can be reduced in the washing step after coagulation. The powder recovery method can be appropriately selected so that the desired remaining state is obtained when the polymer (C) is added to the thermoplastic resin.

[0087] The spray drying method, which is a direct drying method, is a method in which the latex of the polymer (C) is sprayed in the form of fine droplets in a dryer and dried by applying a heated gas for drying. Examples of methods for generating fine droplets include a rotating disk type, a pressure nozzle type, a two-fluid nozzle type, and a pressurized two-fluid nozzle type. The capacity of the dryer may be any of a small capacity for laboratory use and a large capacity for industrial use. The temperature of the heating gas for drying is preferably 200°C or less, more preferably 120 to 180°C. Two or more types of graft copolymer latexes produced separately can also be spray-dried together. In order to improve powder properties such as blocking during spray drying and bulk density, an optional component such as silica can also be added to the latex of the polymer (C) and spray-dried.

[0088] The coagulation method is a method in which the latex of polymer (C) is coagulated, and the polymer (C) is separated, recovered, and dried. The latex of polymer (C) is put into hot water in which a coagulant has been dissolved, and polymer (C) is separated by salting out and coagulation. The separated wet polymer (C) is dehydrated, etc., and polymer (C) with a reduced water content is recovered. The recovered polymer (C) is dried using a squeeze dehydrator or a hot air dryer.

[0089] Examples of the coagulant include inorganic salts such as aluminum chloride, aluminum sulfate, sodium sulfate, magnesium sulfate, sodium nitrate, and calcium acetate; acids such as sulfuric acid; and calcium acetate is preferred. The coagulant may be used alone or in combination of two or more.

[0090] When the coagulant is used as an aqueous solution, the concentration of the aqueous coagulant solution is preferably 0.1% by mass or more, more preferably 1% by mass or more, from the viewpoint of stably coagulating and recovering the polymer (C). The concentration of the aqueous coagulant solution is preferably 20% by mass or less, more preferably 15% by mass or less, from the viewpoint of reducing the amount of coagulant remaining in the recovered polymer (C) and preventing deterioration of the molded appearance of the molded product. The above upper and lower limits can be arbitrarily combined. For example, 0.1 to 20% by mass is preferable, and 1 to 15% by mass is more preferable. The amount of the aqueous coagulant solution is not particularly limited, and is preferably 10 parts by mass or more and 500 parts by mass or less per 100 parts by mass of the latex of the polymer (C).

[0091] The method for contacting the latex of the polymer (C) with the aqueous coagulant solution is not particularly limited, and the following methods can be mentioned. (1) A method in which latex is continuously added to an aqueous coagulant solution while stirring it and then maintained for a certain period of time; (2) A method in which an aqueous coagulant solution and latex are continuously poured into a vessel equipped with a stirrer at a constant ratio and brought into contact with each other, and a mixture containing the coagulated polymer and water is continuously withdrawn from the vessel. The temperature when the latex is contacted with the aqueous coagulant solution is not particularly limited, and is preferably 30° C. or higher and 100° C. or lower. The contact time is not particularly limited.

[0092] The coagulated polymer (C) is washed with water in an amount of about 1 to 100 times by mass of the polymer (C) and filtered. The wet polymer (C) filtered off is dried using a fluidized dryer, a squeeze dehydrator, or the like. The drying temperature and drying time may be appropriately determined depending on the polymer (C) to be obtained. The polymer (C) discharged from the squeeze dehydrator or extruder may be sent directly to an extruder or molding machine for producing a resin composition without being recovered, and mixed with a thermoplastic resin to obtain a molded product.

[0093] The obtained polymer (C) can be dried to obtain a powder of the polymer (C), and the amount of alkali metal atoms in the powder of the polymer (C) can be increased by treating it with an alkali metal salt solution. Specifically, deionized water is added to the powder of the polymer (C) and stirred, then an aqueous solution of an alkali metal salt is added and stirred, and then the mixture is filtered, washed, dehydrated, and dried to obtain a powder of the polymer (C) containing more alkali metal atoms. The amount of alkali metal atoms contained in the powder of the polymer (C) tends to increase by increasing the alkali metal salt concentration of the alkali metal salt solution.

[0094] The proportion of polyorganosiloxane (A1) in 100% by mass of polymer (C) is preferably less than 100% by mass, more preferably 98% by mass or less. The proportion of polyorganosiloxane (A1) in 100% by mass of polymer (C) is preferably 50% by mass or more, more preferably 70% by mass or more, even more preferably 90% by mass or more, and particularly preferably 95% by mass or more. The above upper and lower limits can be arbitrarily combined. For example, 50% by mass or more and less than 100% by mass is preferred, 70% by mass or more and less than 100% by mass is more preferred, 70 to 98% by mass is more preferred, 90 to 98% by mass or more is particularly preferred, and 95 to 98% by mass or more is particularly preferred. If the proportion of polyorganosiloxane (A1) is the lower limit or more, the impact strength of the molded article is excellent. If the proportion is the upper limit or less, the colored appearance of the molded article is excellent.

[0095] The proportion of polymer (A) in 100% by mass of polymer (C) is preferably 60% by mass or more, more preferably 70% by mass or more. The proportion of polymer (A) in 100% by mass of polymer (C) is preferably 95% by mass or less, more preferably 90% by mass or less. The above upper and lower limits can be arbitrarily combined. For example, 60 to 95% by mass is preferred, and 70 to 90% by mass is more preferred. When the content of polymer (A) is equal to or more than the lower limit, the impact strength and flame retardancy of the molded article are excellent. When the content is equal to or less than the upper limit, the dispersibility of polymer (C) in the thermoplastic resin is excellent, and the appearance of the obtained molded article is excellent.

[0096] The proportion of the graft portion in 100% by mass of the polymer (C) is preferably 5% by mass or more, more preferably 7.5% by mass or more, and even more preferably 10% by mass or more. The proportion of the graft portion in 100% by mass of the polymer (C) is preferably 20% by mass or less, more preferably 17.5% by mass or less, and even more preferably 15% by mass or less. The above upper and lower limits can be arbitrarily combined. For example, 5 to 20% by mass is preferable, 7.5 to 17.5% by mass is more preferable, and 10 to 15% by mass is even more preferable. When the content of the graft portion is equal to or more than the lower limit, the dispersibility of the polymer (C) in the thermoplastic resin is excellent, and the appearance of the obtained molded article is excellent. When the content is equal to or less than the upper limit, the impact strength of the molded article is excellent.

[0097] The proportion of the vinyl polymer (B) in 100% by mass of the polymer (C) is preferably 5% by mass or more, more preferably 10% by mass or more. The proportion of the vinyl polymer (B) in 100% by mass of the polymer (C) is preferably 40% by mass or less, more preferably 35% by mass or less. The upper and lower limits can be arbitrarily combined. For example, 5 to 40% by mass is preferred, and 10 to 35% by mass is more preferred. When the content of the vinyl polymer (B) is equal to or more than the lower limit, the dispersibility of the polymer (C) in the thermoplastic resin is excellent, and the appearance of the obtained molded article is excellent. When the content is equal to or less than the upper limit, the impact strength of the molded article is excellent.

[0098] <Resin composition> A resin composition according to one embodiment of the present invention (hereinafter also referred to as "the resin composition") contains a polymer (C) and a thermoplastic resin (hereinafter also referred to as "thermoplastic resin (D)").

[0099] The thermoplastic resin (D) is not particularly limited, and examples thereof include engineering plastics (such as aromatic polycarbonates), styrene-based resins, polyester resins, olefin-based resins (such as polyethylene), thermoplastic elastomers, biodegradable resins, halogen-based resins (such as vinyl chloride resins), and acrylic resins.

[0100] As the engineering plastic, various known thermoplastic engineering plastics can be used without any particular limitation. Examples of engineering plastics include polyphenylene ether, polycarbonate, polyester polymers (polyethylene terephthalate, polybutylene terephthalate, etc.), syndiotactic polystyrene, nylon polymers (6-nylon, 6,6-nylon, etc.), polyarylate, polyphenylene sulfide, polyether ketone, polyether ether ketone, polysulfone, polyether sulfone, polyamide imide, polyether imide, and polyacetal.

[0101] For example, special styrene-based resins such as heat-resistant ABS and heat-resistant acrylic resins that require high heat resistance and melt fluidity are also included as engineering plastics in the present invention. When strength expression is required, aromatic polycarbonate and polybutylene terephthalate are more preferable. Examples of aromatic polycarbonates include 4,4'-dioxydiarylalkane polycarbonates such as 4,4'-dihydroxydiphenyl-2,2-propane (bisphenol A) polycarbonate.

[0102] Examples of olefin resins include high density polyethylene, medium density polyethylene, low density polyethylene, copolymers of ethylene and other α-olefins, polypropylene, copolymers of propylene and other α-olefins, polybutene, and poly-4-methylpentene-1.

[0103] Examples of the thermoplastic elastomer include styrene-based elastomers, urethane-based elastomers, polyolefin-based elastomers, polyamide-based elastomers, fluorine-based elastomers, chlorinated PE-based elastomers, and acrylic-based elastomers.

[0104] Examples of styrene-based elastomers include styrene-butadiene-styrene copolymer (SBS), styrene-isoprene-styrene copolymer (SIS), styrene-ethylene-butene copolymer (SEB), styrene-ethylene-propylene copolymer (SEP), styrene-ethylene-butene-styrene copolymer (SEBS), styrene-ethylene-propylene-styrene copolymer (SEPS), styrene-ethylene-ethylene-propylene-styrene copolymer (SEEPS), styrene-butadiene-butylene-styrene copolymer (partially hydrogenated styrene-butadiene-styrene copolymer: SBBS), partially hydrogenated SIS copolymer, and partially hydrogenated styrene-isoprene-butadiene-styrene copolymer. "-" indicates that the monomers that form the units connected by "-" are copolymerized, and "·" indicates that the monomers are randomly modified by hydrogenation or the like after copolymerization.

[0105] Examples of urethane-based elastomers include reaction products of polymeric diols, organic diisocyanates, and chain extenders. Examples of the polymer diol include polyester diol, polyether diol, polyester ether diol, polycarbonate diol, and polyester polycarbonate diol. Examples of organic diisocyanates include 4,4'-diphenylmethane diisocyanate, toluene diisocyanate, p-phenylene diisocyanate, xylylene diisocyanate, naphthalene diisocyanate, hydrogenated 4,4'-diphenylmethane diisocyanate (4,4'-dicyclohexylmethane diisocyanate), isophorone diisocyanate, and hexamethylene diisocyanate, with 4,4'-diphenylmethane diisocyanate being preferred. Examples of chain extenders include ethylene glycol, diethylene glycol, 1,4-butanediol, 1,5-pentanediol, 2-methyl-1,3-propanediol, 1,6-hexanediol, neopentyl glycol, 1,9-nonanediol, cyclohexanediol, and 1,4-bis(β-hydroxyethoxy)benzene.

[0106] Examples of polyolefin elastomers include ethylene-propylene rubber, ethylene-propylene-diene rubber, ethylene-vinyl acetate copolymer, butyl rubber, butadiene rubber, propylene-butene copolymer, and ethylene-acrylic acid ester copolymer.

[0107] Examples of styrene-based resins include polystyrene, acrylonitrile-styrene copolymers, acrylonitrile-styrene-α-methylstyrene copolymers, acrylonitrile-methyl methacrylate-styrene-α-methylstyrene copolymers, ABS resins, AS resins, MABS resins, MBS resins, AAS resins, AES resins, acrylonitrile-butadiene-styrene-α-methylstyrene copolymers, acrylonitrile-methyl methacrylate-butadiene-styrene-α-methylstyrene copolymers, styrene-maleic anhydride copolymers, styrene-maleimide copolymers, styrene-N-substituted maleimide copolymers, acrylonitrile-styrene-N-substituted maleimide copolymers, acrylonitrile-butadiene-styrene-β-isopropenylnaphthalene copolymers, and acrylonitrile-methyl methacrylate-butadiene-styrene-α-methylstyrene-maleimide copolymers.

[0108] The polyester resin is a polymer of a polybasic acid and a polyhydric alcohol, and is not particularly limited as long as it has thermoplastic properties. Examples of the polybasic acid include terephthalic acid, naphthalic dicarboxylic acid, cyclohexyl dicarboxylic acid, and esters thereof. Examples of the polyhydric alcohol include ethylene glycol, propylene glycol, butanediol, pentanediol, neopentyl glycol, hexanediol, octanediol, decanediol, cyclohexane dimethanol, hydroquinone, bisphenol A, 2,2-bis(4-hydroxyethoxyphenyl)propane, 1,4-dimethyloltetrabromobenzene, and tetrabromobisphenol A bis(2-hydroxyethyl)ether (TBA-EO). The polyester resin may be a homopolymer, a copolymer, or a blend of two or more thereof. As the polyester resin, a commercially available product such as "PETG" manufactured by Eastman Chemical Company may be used.

[0109] Examples of biodegradable resins include microbial polymers, chemically synthesized polymers, and natural product polymers. Examples of microbial polymers include biopolyesters such as polyhydroxybutyrate / valerate (PHB / V), bacterial cellulose, and microbial polysaccharides (pullulan, curdlan, etc.). Examples of chemically synthesized polymers include aliphatic polyesters (polycaprolactone, polybutylene succinate, polyethylene succinate, polyglycolic acid, polylactic acid, etc.), polyvinyl alcohol, and polyamino acids (PMLG, etc.). Examples of natural polymers include chitosan, cellulose, starch, and cellulose acetate.

[0110] Examples of halogen-based resins include vinyl chloride resins such as vinyl chloride homopolymers, copolymers containing 80% or more by mass of vinyl chloride, and highly chlorinated polyvinyl chloride. In addition to vinyl chloride, copolymer components include monovinylidene compounds such as ethylene, vinyl acetate, methyl methacrylate, and butyl acrylate. The proportion of structural units derived from these compounds in the copolymer may be 20% by mass or less. Examples of halogen-based resins include vinyl chloride resins, as well as fluorinated polymers, brominated polymers, and iodinated polymers.

[0111] Examples of the acrylic resin include copolymers of methyl methacrylate and a copolymerizable vinyl monomer. Examples of the copolymerizable vinyl monomer include alkyl acrylates such as methyl acrylate, ethyl acrylate, i-propyl acrylate, n-butyl acrylate, and 2-ethylhexyl acrylate, alkyl methacrylates such as ethyl methacrylate, propyl methacrylate, and n-butyl methacrylate, and aromatic vinyl compounds such as styrene, α-methylstyrene, and vinyl toluene.

[0112] The thermoplastic resin (D) also includes polymer alloys of engineering plastics such as polyester resins, such as polyphenylene ether, polycarbonate, polyethylene terephthalate, and polybutylene terephthalate, polyamide resins, such as syndiotactic polystyrene, 6-nylon and 6,6-nylon, polyarylate, polyphenylene sulfide, polyether ketone, polyether ether ketone, polysulfone, polyether sulfone, polyamide imide, polyether imide, and polyacetal, with other thermoplastic resins.

[0113] The thermoplastic resin (D) can be used alone or in combination of two or more kinds. The thermoplastic resin (D) preferably contains at least one selected from the group consisting of aromatic polycarbonate, polymethyl methacrylate, styrene-acrylonitrile copolymer, polyethylene terephthalate, polybutylene terephthalate, polyvinyl chloride, polyphenylene sulfide, and polyacetal, and more preferably contains at least one selected from the group consisting of polymethyl methacrylate and styrene-acrylonitrile copolymer, because these resins are industrially easily available and have an excellent balance between impact strength and colorability of the molded product.

[0114] In addition to the above, the present resin composition may contain various well-known additives within the scope of not impairing the object of the present invention. Examples of additives include flame retardants (e.g., phosphorus-based, bromine-based, silicone-based, and organic metal salt-based), anti-drip agents (e.g., fluorinated polyolefins, silicones, and aramid fibers), lubricants (e.g., long-chain fatty acid metal salts such as magnesium stearate), release agents (e.g., pentaerythritol tetrastearate), nucleating agents, antistatic agents, stabilizers (e.g., phenolic stabilizers, phosphorus-based stabilizers, ultraviolet absorbers, and amine-based light stabilizers), fillers (e.g., titanium oxide, talc, mica, kaolin, calcium carbonate, and glass flakes), plasticizers, reinforcing agents (e.g., glass fibers, carbon fibers), dyes, and pigments. In the present invention, the presence of the polymer (C) tends to improve the flame retardancy of the resin composition, so that high flame retardancy can be obtained without adding a flame retardant or by adding a small amount of the flame retardant.

[0115] Examples of the dye or pigment include inorganic pigments such as iron oxide, ultramarine, titanium oxide, and carbon black. Examples of the organic pigment include blue pigments such as phthalocyanine and anthraquinone, red pigments such as perylene and quinacridone, and yellow pigments such as isoindolinone. Examples of the special pigment include fluorescent pigments, metal powder pigments, and pearl pigments. Examples of the dye include nigrosine, perinone, and anthraquinone dyes. Various grades of dyes and pigments are commercially available according to the required color, and they can be used, and one type can be used alone, or two or more types can be used in combination.

[0116] The proportion of the polymer (C) in 100% by mass of the present resin composition is not particularly limited, and is preferably 0.5% by mass or more, more preferably 1% by mass or more, and even more preferably 2% by mass or more. The proportion of the polymer (C) in 100% by mass of the present resin composition is preferably 30% by mass or less, and more preferably 20% by mass or less. The above upper and lower limits can be arbitrarily combined. For example, 0.5 to 30% by mass is preferred, 1 to 30% by mass is more preferred, and 2 to 20% by mass is even more preferred. When the proportion of the polymer (C) is equal to or more than the lower limit, the impact strength of the obtained molded article is excellent. When the proportion is equal to or less than the upper limit, the decrease in the flowability and heat distortion temperature of the resin composition can be suppressed.

[0117] The proportion of the thermoplastic resin (D) in 100% by mass of the present resin composition is not particularly limited, and is preferably 40% by mass or more, more preferably 50% by mass or more. The proportion of the thermoplastic resin (D) in 100% by mass of the present resin composition is preferably 99.5% by mass or less, more preferably 99% by mass or less, and even more preferably 98% by mass or less. The above upper and lower limits can be arbitrarily combined. For example, 40 to 99.5% by mass is preferred, 40 to 99% by mass is more preferred, and 50 to 98% by mass is even more preferred. When the proportion of the thermoplastic resin (D) is equal to or greater than the lower limit, the flowability and heat distortion temperature of the resin composition can be suppressed from decreasing. When the proportion is equal to or less than the upper limit, the impact strength of the resulting molded article is excellent.

[0118] (Method of producing resin composition) The resin composition can be produced by mixing the polymer (C), the thermoplastic resin (D), and, if necessary, additives. The method for mixing the materials includes known blending methods, and is not particularly limited. For example, the materials may be mixed and kneaded using a tumbler, a V-type blender, a super mixer, a Nauta mixer, a Banbury mixer, a kneading roll, an extruder, or the like. An example of a method for producing the resin composition of the present invention is a method in which the polymer (C), the pellet-like thermoplastic resin (D), and, if necessary, additives are mixed using an extruder, extruded into a strand shape, and cut into pellets using a rotary cutter, etc. By this method, a pellet-like resin composition can be obtained.

[0119] <Molded body> The molded article according to one embodiment of the present invention (hereinafter also referred to as "the present molded article") contains a polymer (C) and a thermoplastic resin (D). The molded article may further contain other components, such as known components. The present molded article is preferably made of the present resin composition.

[0120] The present molded article can be produced, for example, by molding the present resin composition. The molding method may be any molding method used for molding a thermoplastic resin composition, such as injection molding, extrusion molding, blow molding, or calendar molding.

[0121] The molded article can be widely used industrially as various materials in the fields of automobiles, office automation equipment, home appliances, electrical and electronics, architecture, lifestyle and cosmetics, and medical supplies. More specifically, it can be used as housings for electronic devices, various parts, coating materials, automobile structural members, automobile interior parts, light reflectors, building structural members, and fittings. More specifically, it can be used as interior and exterior members for personal computer housings, mobile phone housings, portable information terminal housings, portable game machine housings, printers, copiers, and the like, conductor coating materials, automobile interior and exterior members, building exterior members, resin window frame members, flooring materials, and piping members. EXAMPLES

[0122] The present invention will be specifically described below with reference to examples and comparative examples. Prior to the examples, various evaluation methods and polyorganosiloxane latex production examples 1-1 to 1-6 will be described. Examples 1-1 to 1-6 and comparative examples 1-1 to 1-7 are examples relating to the production and evaluation of graft copolymers, and Examples 2-1 to 2-9 and comparative examples 2-1 to 2-8 are examples relating to the production and evaluation of thermoplastic resin compositions. In the production examples and examples, "parts", "%" and "ppm" mean "parts by mass", "% by mass" and "ppm by mass" unless otherwise specified.

[0123] <Solid content> A mass w1 of polyorganosiloxane latex is dried in a hot air dryer at 180°C for 30 minutes, the mass w2 of the residue after drying is measured, and the solid content [%] is calculated using the following formula. Solid content [%] = w2 / w1 × 100

[0124] <Particle size> The "polyorganosiloxane (A1) latex" or the "polymer (C) latex" was diluted with deionized water to a solid content concentration of about 3%. The number average particle diameter Dn and the mass average particle diameter Dw were measured using a particle size distribution analyzer CHDF2000 manufactured by MATEC Corporation, USA, under the following conditions. Cartridge: Dedicated capillary cartridge for particle separation (product name: C-202), Carrier fluid: Dedicated carrier fluid (product name: 2XGR500), Carrier liquid: neutral, Carrier liquid flow rate: 1.4 mL / min; Carrier fluid pressure: 4,000 psi (2,600 kPa), Measurement temperature: 35℃, Sample volume used: 0.1mL.

[0125] <Residual metal amount> Approximately 0.25 g of the sample was weighed out, 8 mL of nitric acid and 2 mL of hydrogen fluoride water were added, and the sample was decomposed using microwaves (wet decomposition). The test solution was then made up to 50 mL with distilled water, and the amount of remaining metal was quantified using an ICP emission spectrometer (Thermo iCAP7400 Duo).

[0126] <Thermal decomposition> The graft copolymer was subjected to thermogravimetric analysis using a TG / DTA6200 (manufactured by Seiko Instruments Inc.), and the thermal decomposition property was evaluated by the following method.

[0127] Under conditions of a nitrogen flow rate of 200 mL / min, the sample temperature was raised to 550°C at 10°C / min, and the remaining amount at each temperature was calculated using the following formula (1). Samples with a remaining amount of 1% or less at the end of the test were rated A, and those with a remaining amount of 1% or less were rated B. For samples with a thermal decomposition property of A, the thermal decomposition property was calculated using the following formula (2). The smaller the value calculated by (2), the shorter the time required from the start to the end of thermal decomposition, and the better the thermal decomposition property. Remaining amount (%) = mass after holding (g) / mass of starting material (g) Equation (1) Thermal decomposition (℃) = ((Temperature at 70% remaining amount) - (Temperature at 1% remaining amount) Equation (2)

[0128] (Polymer manufacturing method) [Production Example 1-1: Production of polyorganosiloxane latex (S-1)] 2 parts of γ-methacryloyloxypropyldimethoxymethylsilane (DSMA) and 98 parts of octamethylcyclotetrasiloxane (product name: TSF404, manufactured by Momentive Performance Materials Japan, Inc.) were mixed to obtain 100 parts of an organosiloxane mixture. An aqueous solution of 1 part of sodium dodecylbenzenesulfonate (DBSNa) dissolved in 150 parts of deionized water was added to the organosiloxane mixture, and the mixture was stirred at 10,000 rpm for 5 minutes with a homomixer, and then passed through a homogenizer twice at a pressure of 20 MPa to obtain a stable premixed emulsion.

[0129] The obtained emulsion was placed in a 5-liter separable flask equipped with a cooling condenser, and then the emulsion was heated to 80°C, and a mixture of 0.20 parts of sulfuric acid and 49.8 parts of distilled water was continuously added over a period of 3 minutes. The state of being heated to 80°C was maintained for 7 hours to cause a polymerization reaction, and then the reaction mixture was cooled to room temperature (25°C), and the reaction mixture was kept at room temperature for 6 hours. A 5% aqueous solution of sodium hydroxide was added to the reaction mixture to neutralize the reaction liquid to pH 7.0, and polyorganosiloxane latex (S-1) was obtained.

[0130] The polyorganosiloxane latex (S-1) had a solid content of 30.2% by mass, a number average particle diameter (Dn) of 384 nm, a mass average particle diameter (Dw) of 403 nm, and a Dw / Dn ratio of 1.05.

[0131] [Production Example 1-2: Production of polyorganosiloxane latex (S-2)] Except for changing the composition of the organosiloxane mixture to the composition shown in Table 1, the same operation as in Production Example 1-1 was carried out to obtain a polyorganosiloxane latex (S-2). The polyorganosiloxane latex (S-2) had a solid content of 30.4% by mass, a number average particle diameter (Dn) of 384 nm, a mass average particle diameter (Dw) of 403 nm, and a Dw / Dn ratio of 1.05.

[0132] [Production Example 1-3: Production of polyorganosiloxane latex (S-3)] Except for changing the composition of the organosiloxane mixture to the composition shown in Table 1, the same procedure as in Production Example 1-1 was carried out to obtain a polyorganosiloxane latex (S-3). The polyorganosiloxane latex (S-3) had a solid content of 30.6% by mass, a number average particle diameter (Dn) of 384 nm, a mass average particle diameter (Dw) of 403 nm, and a Dw / Dn ratio of 1.05.

[0133] [Production Example 1-4: Production of polyorganosiloxane latex (S-4)] Except for changing the composition of the organosiloxane mixture to the composition shown in Table 1, the same operation as in Production Example 1-1 was carried out to obtain a polyorganosiloxane latex (S-4). The polyorganosiloxane latex (S-4) had a solid content of 30.8% by mass, a number average particle diameter (Dn) of 384 nm, a mass average particle diameter (Dw) of 403 nm, and a Dw / Dn ratio of 1.05.

[0134] [Production Example 1-5: Production of polyorganosiloxane latex (S-5)] 0.5 parts of γ-methacryloyloxypropyldimethoxymethylsilane (DSMA), 2 parts of tetraethoxysilane (TEOS), and 97.5 parts of octamethylcyclotetrasiloxane (Shin-Etsu Silicone Co., Ltd., product name: DMC, a mixture of cyclic organosiloxanes with 3 to 6 membered rings) were mixed to obtain 100 parts of an organosiloxane mixture. An aqueous solution of 0.68 parts of sodium dodecylbenzenesulfonate (DBSNa) and 0.68 parts of dodecylbenzenesulfonic acid (DBSH) dissolved in 150 parts of deionized water was added to the organosiloxane mixture, and the mixture was stirred at 10,000 rpm for 5 minutes with a homomixer, and then passed through a homogenizer twice at a pressure of 20 MPa to obtain a stable premixed emulsion.

[0135] The obtained emulsion was placed in a 5-liter separable flask equipped with a cooling condenser, and then heated to 80°C and maintained for 5 hours to carry out a polymerization reaction. The emulsion was then cooled to room temperature (25°C), and the resulting reaction product was maintained at room temperature for 6 hours. A 5% aqueous solution of sodium hydroxide was added to the resulting reaction product to neutralize the reaction liquid to pH 7.0, and a polyorganosiloxane latex (S-5) was obtained.

[0136] The polyorganosiloxane latex (S-5) had a solid content of 33.0% by mass, a number average particle diameter (Dn) of 64 nm, a mass average particle diameter (Dw) of 248 nm, and a Dw / Dn ratio of 3.88.

[0137] [Production Example 1-6: Production of polyorganosiloxane latex (S-6)] A polyorganosiloxane latex (S-6) was obtained by carrying out the same operation as in Production Example 1-1, except that the composition of the organosiloxane mixture was changed to the composition shown in Table 1 and the amount of sodium dodecylbenzenesulfonate (DBSNa) was increased to 1.5 parts.

[0138] The polyorganosiloxane latex (S-6) had a solid content of 30.8% by mass, a number average particle diameter (Dn) of 38 nm, a mass average particle diameter (Dw) of 276 nm, and a Dw / Dn ratio of 7.26.

[0139] The ingredients of Production Examples 1-1 to 1-6 are shown in Table 1. The abbreviations in Table 1 are as follows. TSF404: Octamethylcyclotetrasiloxane DMC: A mixture of cyclic organosiloxanes with 3 to 6 ring members. DSMA: γ-methacryloyloxypropyldimethoxymethylsilane TEOS: Tetraethoxysilane

[0140] [Table 1]

[0141] [Example 1-1] 80 parts of the polyorganosiloxane latex (S-1) obtained in Production Example 1-1 (10.0 parts in terms of polymer) was placed in a 5-liter separable flask, and a mixture of 8.82 parts of butyl acrylate (BA), 0.18 parts of allyl methacrylate (AMA), and 0.16 parts of cumene hydroperoxide (CB) was added thereto, and the mixture was stirred at room temperature for 1 hour to impregnate the polyorganosiloxane.

[0142] The atmosphere in the flask was replaced with nitrogen by passing a nitrogen gas flow, and the liquid temperature was raised to 50°C. When the liquid temperature reached 50°C, an aqueous solution of 0.001 parts of ferrous sulfate (Fe), 0.003 parts of disodium ethylenediaminetetraacetate (EDTA), and 0.24 parts of sodium formaldehyde sulfoxylate (SFS) dissolved in 10 parts of deionized water was added to initiate radical polymerization. After the dropwise addition was completed, the liquid temperature was maintained at 65°C for 1 hour to complete the polymerization of the acrylate component, and a composite rubber latex of polyorganosiloxane and poly-n-butyl acrylate was obtained.

[0143] The liquid temperature of the obtained composite rubber latex was set to 65°C, and a mixture of 11.0 parts of methyl methacrylate (MMA) and 0.24 parts of cumene hydroperoxide (CB) was dropped into the latex over one hour to initiate a graft polymerization reaction. After the dropwise addition was completed, the temperature was maintained at 65°C for one hour, and then cooled to room temperature to obtain a latex of polyorganosiloxane-containing graft copolymer (G-1).

[0144] 500 parts of an aqueous solution of calcium acetate having a concentration of 1% by mass was heated to 85° C., and 340 parts of the latex of graft copolymer (G-1) was gradually dropped into the solution while stirring to coagulate it. The obtained graft copolymer (G-1) was filtered, washed, dehydrated, and then dried to obtain graft copolymer (G-1).

[0145] 10 parts of the obtained graft copolymer (G-1) was added to 141 parts of deionized water and stirred for 3 minutes, and then 10 parts of a 10% by mass aqueous sodium chloride solution was added and stirred for 3 minutes. The graft copolymer (A-1) was filtered, washed, dehydrated, and then dried to obtain a powder of the graft copolymer (A-1) containing sodium. The mass average particle size, alkali metal content and thermal decomposition property of the obtained graft copolymer powder (A-1) were measured by the above-mentioned methods. The obtained results are shown in Table 2.

[0146] [Examples 1-2 to 1-4] Polyorganosiloxane-containing graft copolymers (G-2 to G-4) were produced in the same manner as in Example 1-1, except that the raw material compositions used in Example 1-1 were changed to the conditions shown in Table 2. Graft copolymer powders (A-2 to A-4) were also obtained and similar measurements were performed. The results are shown in Table 2.

[0147] [Examples 1-5] In the same manner as in Example 1-1, polyorganosiloxane-containing graft copolymer (G-1) was produced, and the amount of the aqueous solution with a concentration of 10% by mass of sodium chloride was changed to 20 parts, and the powder of graft copolymer (A-5) was obtained in the same manner as in Example 1-1, and the same measurement was carried out. The obtained results are shown in Table 2.

[0148] [Examples 1-6] In the same manner as in Example 1-1, polyorganosiloxane-containing graft copolymer (G-1) was produced, and the amount of the aqueous solution with a concentration of 10% by mass of sodium chloride was changed to 50 parts, and the powder of graft copolymer (A-6) was obtained in the same manner as in Example 1-1, and the same measurement was carried out. The obtained results are shown in Table 2.

[0149] [Comparative Example 1-1] Except that the polyorganosiloxane-containing graft copolymer (G-1) was not treated with sodium chloride solution after obtaining, the polyorganosiloxane-containing graft copolymer powder (A-7) was obtained in the same manner as in Example 1-1, and the same measurement was carried out. The obtained results are shown in Table 2.

[0150] [Comparative Example 1-2] After obtaining polyorganosiloxane-containing graft copolymer (G-2), the same method as in Example 1-2 was used to obtain polyorganosiloxane-containing graft copolymer powder (A-8), and the same measurement was carried out, except that the treatment with sodium chloride solution was not carried out after obtaining polyorganosiloxane-containing graft copolymer (G-2). The obtained results are shown in Table 2.

[0151] [Comparative Example 1-3] After obtaining polyorganosiloxane-containing graft copolymer (G-3), the same method as in Example 1-3 was used to obtain polyorganosiloxane-containing graft copolymer powder (A-9), and the same measurement was carried out, except that the treatment with sodium chloride solution was not carried out after obtaining polyorganosiloxane-containing graft copolymer (G-3). The obtained results are shown in Table 2.

[0152] [Comparative Example 1-4] After obtaining polyorganosiloxane-containing graft copolymer (G-4), the treatment with sodium chloride solution was not carried out, and the same measurement was carried out in the same manner as in Example 1-4 to obtain polyorganosiloxane-containing graft copolymer powder (A-10). The obtained results are shown in Table 2.

[0153] [Comparative Example 1-5] A polyorganosiloxane-containing graft copolymer (G-5) was produced in the same manner as in Example 1-1, except that the raw material compositions used in Example 1-1 were changed to the conditions shown in Table 2, and a graft copolymer powder (A-11) was obtained and similar measurements were performed. The results obtained are shown in Table 2.

[0154] [Comparative Example 1-6] After obtaining polyorganosiloxane-containing graft copolymer (G-5) by the method described in Comparative Example 1-5, add 10 parts of obtained graft copolymer (G-5) to 141 parts of deionized water, stir for 3 minutes, add 10 parts of aqueous solution of sodium chloride with a concentration of 10% by mass, stir for 3 minutes, filter, wash, dehydrate, and then dry to obtain sodium-containing graft copolymer powder (A-12), and carry out the same measurement.The obtained results are shown in Table 2.

[0155] [Comparative Example 1-7] Except for changing the raw material composition used in Example 1-1 to the conditions shown in Table 2, the same procedure as in Example 1-1 was used to obtain polyorganosiloxane-containing graft copolymer (G-6), and then 10 parts of the obtained graft copolymer (G-6) were put into 141 parts of deionized water and stirred for 3 minutes, and then 10 parts of an aqueous solution of sodium chloride with a concentration of 10% by mass was put into and stirred for 3 minutes, and then filtered, washed, dehydrated, and dried to obtain sodium-containing graft copolymer powder (A-13), and the same measurement was carried out.The results obtained are shown in Table 2.

[0156] [Table 2]

[0157] The abbreviations in Table 2 are as follows. nBA: n-butyl acrylate AMA: Allyl methacrylate MMA: Methyl methacrylate Na: Sodium K: Potassium

[0158] Compared with the graft copolymers according to Comparative Examples 1-1 to 1-7, the graft polymers according to Examples 1-1 to 1-6 had improved thermal decomposition properties.

[0159] [Examples 2-1 to 2-9, Comparative Examples 2-1 to 2-8] A mixture was obtained by blending the polyorganosiloxane-containing polymer powder, additives, and thermoplastic resin in the ratios shown in Table 3. This mixture was fed to a devolatilizing twin-screw extruder (manufactured by Ikegai Corporation, PCM-30 (product name)) and kneaded to prepare pellets of each resin composition.

[0160] The following thermoplastic resins were used: PC: polycarbonate resin (Iupilon S-2000F, manufactured by Mitsubishi Engineering Plastics Corporation, viscosity average molecular weight 24,000). The following additives were used: A-3750: Acrylic modified PTFE (Metabrene A-3750, manufactured by Mitsubishi Chemical Corporation).

[0161] Pellets of the resin composition were injection molded using an injection molding machine (SE100DU (product name), manufactured by Sumitomo Heavy Industries, Ltd.) to prepare test pieces for evaluation. Specimen specifications: Test piece A: Length 80mm x Width 10mm x Thickness 4mm Test piece B: Length 100mm x Width 50mm x Thickness 2mm Test piece C: Length 125mm x Width 13mm x Thickness 1.6mm The extrusion conditions and injection molding conditions are as follows. Extrusion barrel temperature 280℃, Injection cylinder temperature: 280℃, Mold temperature: 60℃.

[0162] Test piece A was notched with a Type A notch conforming to ISO 179-1 and the Charpy impact strength was measured. The higher the Charpy impact strength value, the higher the impact resistance. The results are shown in Table 3.

[0163] Test piece B is visually observed for flow marks (striped patterns seen near the gate of a molded article) appearing near the gate of test piece B. "Judgment method" The appearance of the gate part is judged visually (A: Flow marks are not noticeable, B: Flow marks are noticeable). The evaluation results are shown in Table 3.

[0164] Using test piece C, the total burning time and the presence or absence of dripping at the time of ignition of five test pieces were measured using a vertical burning test method conforming to the UL94V test. The shorter the total burning time, the higher the flame retardancy and the more preferable it is for there to be no dripping. The evaluation results are shown in Table 3.

[0165] [Table 3]

[0166] The resin composition according to Comparative Example 2-1 did not contain a graft copolymer, and therefore had low low-temperature impact strength and flame retardancy. The molded articles of Examples 2-1 to 2-9, which contained a polymer containing a specific amount of alkali metal atoms along with a specific particle size, had better flame retardancy than the molded articles of Comparative Examples 2-1 to 2-8. Compared with the graft copolymers of Examples 2-1 to 2-9, the graft copolymers of Comparative Examples 2-6 to 2-7 had smaller particle sizes and therefore were inferior in appearance.

Claims

1. A polyorganosiloxane-containing polymer containing 100 ppm by mass or more of alkali metal atoms, having a mass average particle diameter Dw of 350 nm or more, and being in the form of a powder, The polyorganosiloxane-containing polymer has a composite and a graft portion, The composite includes a polyorganosiloxane and a first vinyl polymer; The graft portion is a polyorganosiloxane-containing polymer comprising a second vinyl polymer.

2. A polyorganosiloxane-containing polymer containing 100 ppm by mass or more of alkali metal atoms, having a mass average particle diameter Dw of 350 nm or more, and in powder form, A polyorganosiloxane-containing polymer, in which the proportion of polyorganosiloxane in 100 mass% of the polyorganosiloxane-containing polymer is 70 mass% or more and 98 mass% or less.

3. The polyorganosiloxane-containing polymer according to claim 1 or 2, having a mass average particle diameter Dw of 1000 nm or less.

4. The polyorganosiloxane-containing polymer according to claim 1, wherein the proportion of the graft portion in 100% by mass of the polyorganosiloxane-containing polymer is 5% by mass or more and 20% by mass or less.

5. The polyorganosiloxane-containing polymer according to claim 1 or 4, wherein the first vinyl polymer contains a structural unit derived from a (meth)acrylate monomer.

6. The polyorganosiloxane-containing polymer according to any one of claims 1, 4 and 5, wherein the second vinyl polymer contains a structural unit derived from a (meth)acrylate monomer.

7. The polyorganosiloxane contains a constituent unit derived from a siloxane-based crosslinking agent, and the proportion of the constituent units derived from the siloxane-based crosslinking agent in 100% by mass of the polyorganosiloxane is 3% by mass or less. The polyorganosiloxane-containing polymer according to any one of claims 1 to 6.

8. The polyorganosiloxane-containing polymer according to any one of claims 1 to 7, wherein the alkali metal atom is a sodium atom.

9. A composition comprising the polyorganosiloxane-containing polymer according to any one of claims 1 to 8 and a thermoplastic resin.

10. A molded article comprising the polyorganosiloxane-containing polymer according to any one of claims 1 to 8 and a thermoplastic resin.

Citation Information

Patent Citations

  • JP1975083448A

  • Flame-retardant resin composition

    JP2003119368A

  • Silicone fine particle excellent in hydrophobicity and alkali resistance, method for producing the same and coating liquid using the same

    JP2009127052A

  • Stress relaxation agent for curable resin, curable resin composition and molding

    JP2015218317A

  • Polyorganosiloxane-containing graft copolymer, thermoplastic resin composition and molding

    JP2020041067A